Effect of pollination by bees and other insects on the production of onion seeds - Witter, Sidia (2003)
Pollination's deficit has been pointed as one of the causes of the low onion seed production. The objective of this work was to evaluate the relationship of the presence of bees and other insects in flowers of two cultivars of onion, Allium cepa L. (Alliaceae), with seed production. The diversity and frequency of insects in flowers of onion was registered and their pollinizing effect was tested. The behavior of Apis mellifera was directly observed in the flowers and the fidelity was testified from the presence of pollen in the corbiculas. Representatives of Hymenoptera and Diptera were the most abundant flower visitors. There was a correlation between frequency of A. mellifera and the number of umbels with flowers in both cultivars and of other insects in Crioula Alto Vale. The production of seeds with free insect visitation had an increase of more than 20% in relation to others without insects and with the visitation of one bee. A. mellifera transported more than 70% of onion pollen. The presence of A. mellifera is indispensable for the commercial production of onion seeds.